Production planning and scheduling in mining scenarios under IPCC mining systems. (March 2020) - Samavati, Mehran; Essam, Daryl; Nehring, Micah; Sarker, Ruhul
Abstract: The open pit mine production scheduling problem (OPMPSP) consists of scheduling material extraction in a mineral deposit over a horizon of several time periods such that the profit of the operation is maximized and a variety of operational constraints are satisfied. These constraints vary depending on the extraction system used by the mining company for extracting material. Two extraction systems are available in the mining industry – Truck and Shovel (T&S) and In-pit Crusher Conveyor (IPCC). IPCC systems offer an alternative to conventional T&S systems by completely replacing trucks with conveyors. This replacement introduces a number of additional sequencing constraints that are not required in traditional T&S systems. These additional constraints add further complexity to an already complex large scale OPMPSP. While OPMPSP has been extensively studied and a number of optimization techniques have been successfully applied, it is very much unresolved when IPCC systems are used; in most cases, industry still relies on the judgement or best estimate of experienced personnel. In this paper, we develop a new integer programming model of OPMPSP-IPCC and present an algorithm to address practical sized instances. The performance of the developed algorithm is also evaluated.